2018
DOI: 10.1007/s00068-018-0959-y
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the use of resuscitative endovascular balloon occlusion of the aorta in the management of major exsanguination

Abstract: BackgroundCirculatory collapse is a leading cause of mortality among traumatic major exsanguination and in ruptured aortic aneurysm patients. Approximately 40% of patients die before hemorrhage control is achieved. Resuscitative endovascular balloon occlusion of the aorta (REBOA) is an adjunct designed to sustain the circulation until definitive surgical or endovascular repair. A systematic review was conducted for the current clinical use of REBOA in patients with hemodynamic instability and to discuss its po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 129 publications
3
106
0
3
Order By: Relevance
“…After subsequent duplication removal, primary and secondary screening analysis based on inclusion and exclusion criteria, 105 articles were included in the study (figure 1). 3 11–70 A large proportion of articles were retrospective. 13 studies were case reports, and 10 were prospective observational studies (figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…After subsequent duplication removal, primary and secondary screening analysis based on inclusion and exclusion criteria, 105 articles were included in the study (figure 1). 3 11–70 A large proportion of articles were retrospective. 13 studies were case reports, and 10 were prospective observational studies (figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The military also describe impressive and successful case reports . A meta‐analysis of REBOA and another of REBOA and open aortic cross clamping together with an early REBOA registry report all suggested positive effects on outcomes and are broadly supportive. There followed a statement from the American College of Surgeons highlighting indications, guidelines and complications.…”
Section: Competing Interestsmentioning
confidence: 88%
“…REBOA is widely considered to be a minimally invasive and safe technique. A recent systematic review reported a rate of iatrogenic injury related to REBOA of < 5% [5]. Meanwhile, the potential risks of REBOA have also been indicated.…”
Section: Discussionmentioning
confidence: 99%